Reading the Bible Differently: African Americans and the Bible - Okoye, James Chukwuma ca. 20./21. Jh. (Journal of black religious thought, 2022)
Reading texts is reading ourselves. The Bible became a language through which the uprooted slaves negotiated a strange new world and the slave existence. As identity and self-interpretation varied, so did the loci of interpretation shift. The essay navigates African American experience in tandem with the loci of their biblical interpretation, ending with reflection on the “hour”—the tasks and biblical loci for the current situation of African Americans.